Dissolution testing of ursodeoxycholic acid suspension using SPE as sample preparation - Boscolo, Oriana (2023)
Objectives: To develop and validate an analytical method by HPLC?UV (High Performance Liquid Chromatography?Ultraviolet) for the quantification of ursodeoxycholic acid suspension in a dissolution test followed by a solid phase extraction (SPE) to circumvent the interference of sodiumlauryl sulphate (SLS) present in the dissolution medium.Methods: United States Pharmacopeia (USP) apparatus 2. The dissolution medium was 900 ml of an aqueous solution of 0.05 M phosphatebuffer (pH 8.4) with 2% SLS. The samples were filtered and cleaned by SPE with 500 mg/3ml C18 cartridges. The analytical method wasvalidated for specificity, linearity, LOD (limit of detection), LOQ (limit of quantification) accuracy and precision. Chromatographic conditions,Symmetry-C18 column (150 mm × 4.6 mm, id; 5 µm particle size), 40°C, 100 µl injection volume and UV detection at 200 nm. The flow rate was1 ml/min using acetonitrile?phosphoric acid (pH 3.0, 0.15 mM) (48:52).Key findings: SPE provided an efficient and selective extraction of ursodeoxycholic acid from the dissolution medium. On the other hand, theSPE washing step allowed the elimination of SLS. The ursodeoxycholic acid method optimisation and validation were accomplished with no lessthan 80% in 30 min.Conclusion: The developed analytical method was simple and adequate for the analysis of ursodeoxycholic acid suspension samples that metthe USP specifications for dissolution test.